Embryonic development of the endangered Caspian brown trout, Salmo trutta caspius (Kessler, 1877). (5th February 2019) - Najafpour, Babak; Dorafshan, Salar; Paykan Heyrati, Fatemeh; Power, Deborah M.
Summary: The Caspian brown trout, Salmo trutta caspius is an endangered species of economic value and better knowledge of its biology will contribute to conservation measures. In the present study we characterized its early development to identify critical embryonic stages, by observing embryos and larvae from a broodstock maintained in captivity incubated at 9 ± 1°C. Morphological analysis of landmark stages of embryonic development revealed that first cleavage occurred at 189 degree‐h, a many‐celled blastoderm formed at 62 degree‐days (dd), a germ ring at 72 dd, the neural keel stage at 88 dd, the blastopore closed at 137 dd, the eye became pigmented at 188 dd and the larvae hatched at 373 dd. The detailed timing of these landmark features will help development of strategies aiming at increased aquaculture production of this species.